STATUS DAN KEDUDUKAN USAHA MIKRO DAN KECIL SETELAH TERDAFTAR SEBAGAI PERSEROAN: The Legal Status and Position of Micro and Small Enterprises After Registering as a Sole Proprietorship Corporation - M. Pasha Arifin Nusantara; Sri Bakti Yunari (Faculty of Law, Universitas Trisakti, 2024)
The government through Law Number 11 of 2020 concerning Job Creation as amended by Law Number 6 of 2023 concerning the Stipulation of Government Regulation in Lieu of Law Number 2 of 2022 concerning Job Creation into Law seeks to encourage ease of doing business, one of which is ease of doing business MSEs. The legal issues in this article are: 1) what is the status and position of an MSE company according to the concept of a sole proprietorship based on the Job Creation Law? 2) what are the responsibilities of the founders and shareholders of the legal entity status towards MSEs for a sole proprietorship company? The research in this thesis is a normative research. The research was conducted using qualitative analysis with deductive conclusions drawn. The result and conclusion of this study is, namely for companies that have legal status, have the status of a legal entity, and their position in the running of the company can use one tier board or multiple boards. The founders and managers of individual companies, there is protection in the form of limitations of responsibility, but if it is carried out without good faith.